Effect of a Biological Additive on Nitrogen Losses from Pig Slurry during Storage. Issue 4 (1st July 2016) - Provolo, Giorgio; Finzi, Alberto; Perazzolo, Francesca; Mattachini, Gabriele; Riva, Elisabetta
Abstract : Additives applied to animal manure slurries can affect the chemical composition and the biological processes of slurries during storage, with possible improvement of their management and reduction of environmental problems. Some new formulations are marketed claiming a nitrogen (N) removal effect due to denitrification, with the consequence of a reduced N content in the manure after storage. This study evaluated the effects of one of these commercial additives (BACTYcomplex) on slurry characteristics and N losses at a commercial piggery. The additive was applied to four different sectors of the piggery, each with an independent under‐floor slurry pit; four other sectors served as controls without treatment. Pits were emptied every 4 wk, and the manure was analyzed for total and ammonia‐N and total and volatile solids. Slurry samples from the last month of the on‐farm assessment were removed and stored thermostatically in vessels external to the piggery. A subsample of slurry that was treated with the additive at the piggery was treated with an additional dose of additive at the beginning of long‐term storage. The additive did not change the composition of the slurry during in‐house storage (4 wk duration). During the 155 d of external thermostatic storage, the total solids content of treated slurry was reduced by 18% compared with control slurry, but the N content and composition of treated slurry was unaffected. The additive had a positive effect in accelerating the stabilization of the slurry but did not modify N losses. Core Ideas: A new biological additive with denitrification enhancement capability was tested. The additive increased the total solids reduction during 6 mo storage of the slurry. The total and ammonia‐N losses were not affected by the additive. The additive promoted stabilization of slurry but did not reduce N content.